Digital forensics and cyber crime second international ICST conference, ICDF2C 2010, Abu Dhabi, United Arab Emirates, October 4-6, 2010, Revised selected papers - International Conference on Digital Forensics and Cyber Crime Abu Dhabi, United Arab Emirates) 2010; Baggili, Ibrahim Moussa; SpringerLink (Online service). (Heidelberg New York Springer, 2011)
This book contains a selection of thoroughly refereed and revised papers from the Second International ICST Conference on Digital Forensics and Cyber Crime, ICDF2C 2010, held October 4-6, 2010 in Abu Dhabi, United Arab Emirates. The field of digital forensics is becoming increasingly important for law enforcement, network security, and information assurance. It is a multidisciplinary area that encompasses a number of fields, including law, computer science, finance, networking, data mining, and criminal justice. The 14 papers in this volume descibe the various applications of this technology and cover a wide range of topics including law enforcement, disaster recovery, accounting frauds, homeland security, and information warfare.
Electronic reproduction.
Keywords: Computer crimes -- Investigation -- Congresses; Computer crimes -- Congresses; Computer security -- Congresses; Computers -- Access control -- Congresses; Electronic books